Analisis Pengaruh Kualitas Produk, Kualitas Pelayanan, Harga, Dan Lokasi Terhadap Pengambilan Keputusan Pembelian Pada Pt. Bumi Agung Perkasa Indah - Josua Lamindo Karo Karo; Dovina Navanti; Franciscus Dwikotjo Sri Sumantyo (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to determine the analysis of the influence of product quality, service quality, price and location on purchasing decisions at PT. Bumi Agung Mighty Beautiful. This type of research is quantitative. The population in this study is unknown. The sampling technique uses Non-Probability Sampling using Purposive Sampling techniques. The sample in this study consisted of 100 respondents. Data collection technique by distributing questionnaires via Google Form. Hypothesis testing in this research uses Multiple Linear Regression analysis. The research subjects are consumers of PT. Bumi Agung Mighty Beautiful. The results of this research show that the variables product quality, service quality, price and location partially and simultaneously have a significant effect and have a positive influence on purchasing decision variables.